How Teacher’s Gender Influence Student’s Gender Identity in Early Childhood - Safiruddin Al Baqi (Jurnal Pendidikan Usia Dini, 2023)
The development of gender identity in early childhood will influence how they accept their gender. Someone who confuses about their gender would be at risk to experience gender dysphoria. This study aimed to determine differences in gender identity among early childhood based on the presence of male and female teachers. The study used a quantitative approach with a cross-sectional study design. Data was collected using gender identity questionnaires from April until August 2023. The sample was 200 students (95 male; 105 female) in 23 preschool institutions (5.83 years old; SD: 0.50) in 5 regencies in East Java. Data from the two groups sample showed a difference in average scores (9.15 for children who had two gender teachers and 7.57 who only had one gender teacher). The results of statistical analysis using the Mann-Whitney U-Test showed a significance value of 0.00. The result shows significant differences in gender identity between the two groups. It shows the importance of the existence of male and female teachers in early childhood education because both have important complementary roles, especially for the children's gender identity. Researchers suggest schools, the government, or other policymakers provide regulations for the presence of male teachers in early childhood education institutions. Keywords: early childhood; gender identity; teacher gender References: Al Baqi, S. (2021). Penguatan Identitas Gender pada Siswa Laki-laki Melalui Kehadiran Guru Laki-laki di Tingkat PAUD [Strengthening Gender Identity in Male Students Through the Presence of Male Teachers at the Early Childhood Education Level]. Martabat: Jurnal Perempuan Dan Anak, 5(2), 289–309. https://doi.org/10.21274/martabat.2021.5.2.289-309 Arikunto, S. (1983). Prosedur penelitian: Suatu pendekatan praktik [Research procedure: A practical approach]. PT. Bina Aksara, Jakarta. https://books.google.co.id/books?id=6PKbAQAACAAJ Azizah, N. (2014). Pengenalan Identitas Gender pada Anak (Studi pada Taman Pendidikan Anak atau Day Care) [Introduction to Gender Identity in Children (Studies in Children's Education Parks or Day Care)]. Yin Yang, 9(1), 47–58. Beek, T. F., Cohen-Kettenis, P. T., & Kreukels, B. P. C. (2015). Gender incongruence/gender dysphoria and its classification history. International Review of Psychiatry, 28(1), 5–12. https://doi.org/10.3109/09540261.2015.1091293 Boddington, Ellen. (2016). A qualitative exploration of gender identity in young people who identify as neither male nor female—ProQuest. May, 134. Bryan, N., & Milton Williams, T. (2017). We need more than just male bodies in classrooms: Recruiting and retaining culturally relevant Black male teachers in early childhood education. Journal of Early Childhood Teacher Education, 38(3), 209–222. https://doi.org/10.1080/10901027.2017.1346529 Bussey, K. (2010). Gender Identity Development. In Handbook of Identity Theory and Research. Springer US. Cervantes, J. C. (2018). Gender Identity in Early Childhood. KnE Life Sciences, 2018, 189–198. https://doi.org/10.18502/kls.v4i8.3276 Coxon, J., & Seal, L. (2021). Medical Management to Support Trans Men In A Gender Identity Clinic. In Men’s Health (pp. 260–265). CRC Press. https://doi.org/10.1201/9780429347238-32 Farquhar, S. (1997). Are Male Teachers Really Necessary? (9 Seiten). Gianesini, G. (2016). Gender Identity. Encyclopedia of Family Studies, 5(10), 1–6. https://doi.org/10.1002/9781119085621.wbefs465 Koch, S., & Farquhar, B. (2015). Breaking through the glass doors: Men working in early childhood education and care with particular reference to research and experience in Austria and New Zealand. European Early Childhood Education Research Journal, 23(3), 380–391. https://doi.org/10.1080/1350293X.2015.1043812 Martin, R. (2017). Gender and Emotion Stereotypes in Children’s Television. Journal of Broadcasting and Electronic Media, 61(3), 499–517. https://doi.org/10.1080/08838151.2017.1344667 Maulana, R. A., Kurniati, E., Yulindrasari, H., No, J. S., Kec, I., Kota, S., & Barat, J. (2020). Apa yang Menyebabkan Rendahnya Keberadaan Guru Laki-laki di PAUD? [ What Causes the Low Presence of Male Teachers in ECE] 15(1), 23–32. Patacchini, E. (2019). Mothers, Peers and Gender-Role Identity Claudia Olivetti, Eleonora Patacchini and Yves Zenou. 1295. Pujisatuti, T. (2014). Peran Orang Tua Dalam Pembentukan Identitas Gender Anak [The Role of Parents in Forming Children's Gender Identity]. Syi’ar, 14(1), 53–61. Qosyasih, N. N. S., & Adriany, V. (2021). Constructing Gender Identity in Young Children. Proceedings of the 5th International Conference on Early Childhood Education (ICECE 2020), 538(Icece 2020), 177–179. https://doi.org/10.2991/assehr.k.210322.038 Salim, R. M. A., & Safitri, S. (2020). Parents as Teachers: The Influence of Internal and External Factors on Parenting Style Differences. Jurnal Psikologi Teori Dan Terapan, 10(2), 95. https://doi.org/10.26740/jptt.v10n2.p95-104 Santrock, J. W. (2011). Life-span Development (13th ed.). McGraw-Hill. Smith, K. E. (1981). Male Teachers in Early Childhood Education: Sex-Role Perceptions. The Humanist Educator, 20(2), 58–64. https://doi.org/10.1002/j.2164-6163.1981.tb00078.x Sovitriana, R. (2020). Kajian Gender Dalam Tinjauan Psikologi [Gender Studies in Psychological Review]. In Angewandte Chemie International Edition, 6(11), 951–952. (Vol. 13, Issue April). Steensma, T. D., Kreukels, B. P. C., de Vries, A. L. C., & Cohen-Kettenis, P. T. (2013). Gender identity development in adolescence. Hormones and Behavior, 64(2), 288–297. https://doi.org/10.1016/j.yhbeh.2013.02.020 Sum, T. A., Tamo, A., & Talu, I. (2003). Faktor penyebab kurangnya minat laki-laki untuk menjadi guru paud di kabupaten manggarai [Factors causing men's lack of interest in becoming early childhood teachers in Manggarai district]. Missio, 10, 192–203. VandenBos, G. R. (2015). APA Second Edition Dictionary of Psychology. American Psychological Association. https://doi.org/10.1515/9783111704227.1 Zucker, K. J., Bradley, S. J., Sullivan, C. B. L., Kuksis, M., Birkenfeld-Adams, A., & Mitchell, J. N. (1993). A Gender Identity Interview for Children. Journal of Personality Assessment, 61(3), 443–456. https://doi.org/10.1207/s15327752jpa6103_2